Flexiwheel / Halimahton Borhan … [et al.] - Borhan, Halimahton; -, Ummi Syafiqah; -, Nurul Husna; -, Nurul Afiqah; -, Nur Izyani; -, Siti Hajar; -, Wan Muhammad Syahmi (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
The ability of an individual to intentionally move around the surroundings is known as mobility. Mobility restrictions have a variety of negative effects on an individual’s health and wellbeing, one of which being an increased chance of disability. To achieve movement, a person with a mobility disability requires assistive technology such as a wheelchair. Introducing the innovation of FLEXIWHEEL, an electric wheelchair with the touch of Artificial Intelligence (AI) technology. The creative use of AI assisting the mobility issues faced by people with disabilities. When navigating different terrain, people with mobility disabilities frequently run across problems like uneven surfaces and steep inclines. Conventional wheelchairs may find it difficult to adjust to these environmental difficulties. However, with the help of AI-powered electric wheelchairs (FLEXIWHEEL) with an adjustable platform will provide a viable way to improve user’s independence and accessibility as well as allowing the options for the user and caregiver to control. Furthermore, this FLEXIWHEEL can customize its navigation system to maximize comfort, safety, and efficiency for every user such as voice commands and touch sensitive controls. In conclusion, with the era of Artificial Intelligence, it is suitable if it is used to help people with disabilities to maximize their shortcomings to the best of our ability rather than misusing it.